1992
DOI: 10.1093/carcin/13.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Reaction product inactivation of aryl sulfotransferase IV following electrophilic substitution by the sulfuric acid ester of N-hydroxy-2-acetylaminofluorene

Abstract: Rat liver N-hydroxy-2-acetylaminofluorene (N-OH-2AAF) sulfotransferase activity is mediated by aryl sulfotransferase IV (AST IV) and causes the bioactivation of N-OH-2AAF to a highly reactive sulfuric acid ester form putatively capable of inducing liver cancer. Dietary administration of 2-acetylaminofluorene (2AAF) to induce hepatocarcinogenesis in rats has been shown to cause a rapid loss in N-OH-2AAF sulfotransferase activity. A possible mechanism for the in vivo loss in sulfotransferase activity may be the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Arylamine. Previous reports have indicated a timedependent irreversible inactivation of AST IV with N-hydroxy-2-acetylaminofluorene (33) and N-hydroxyaniline (7). Therefore, we examined the potential for one of the secondary N-hydroxy arylamines to irreversibly inhibit the enzyme.…”
Section: Assessment Of the Potential For Irreversible Inhibition Of A...mentioning
confidence: 97%
“…Arylamine. Previous reports have indicated a timedependent irreversible inactivation of AST IV with N-hydroxy-2-acetylaminofluorene (33) and N-hydroxyaniline (7). Therefore, we examined the potential for one of the secondary N-hydroxy arylamines to irreversibly inhibit the enzyme.…”
Section: Assessment Of the Potential For Irreversible Inhibition Of A...mentioning
confidence: 97%
“…Our study also showed that these SERMs do not inhibit SULT2A1-catalzyed human liver cytosolic LCA sulfonation by mechanism-based inactivation involving a reactive intermediate. Previous studies reported the inactivation of a rat sulfotransferase enzyme by chemicals such as N-hydroxy-2acetylaminofluorene (Mangold et al, 1990;Ringer et al, 1992). The inactivation of sulfotransferase occurs as a result of the formation of reactive metabolites (formed when the sulfate group is cleaved off and resulting in an electrophilic cation).…”
Section: Discussionmentioning
confidence: 99%